1999
DOI: 10.1161/01.cir.99.7.963
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as Cardiovascular Therapy

Abstract: F or many years, cardiac physicians were strongly influenced by Thomas Hilton's "Rest and Pain" and advocated prolonged rest for the majority of their patients. However, the past 3 decades have seen a complete revolution in this thinking, and moderate to vigorous exercise is now prescribed not only for the prevention of ischemic heart disease 1 but also as a major component of treatment after myocardial infarction, 2 angioplasty and coronary bypass surgery, and heart transplantation 3 and in congenital heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
261
0
59

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(326 citation statements)
references
References 90 publications
6
261
0
59
Order By: Relevance
“…Exercise can also positively influence classical risk factors that are associated with coronary heart disease such as diabetes, hypertension, obesity, dyslipidemias, and endothelial dysfunction (6)(7)(8). The higher respiration rate during severe physical exercise leads to the generation of more free radicals than the endogenous antioxidant systems can scavenge (9), whereas moderate intensity aerobic exercise enhances endothelium dependent vasodilation in humans (10), and attenuates exercise-induced peroxidation (11) and cardiovascular mortality (12) in the elderly.…”
mentioning
confidence: 99%
“…Exercise can also positively influence classical risk factors that are associated with coronary heart disease such as diabetes, hypertension, obesity, dyslipidemias, and endothelial dysfunction (6)(7)(8). The higher respiration rate during severe physical exercise leads to the generation of more free radicals than the endogenous antioxidant systems can scavenge (9), whereas moderate intensity aerobic exercise enhances endothelium dependent vasodilation in humans (10), and attenuates exercise-induced peroxidation (11) and cardiovascular mortality (12) in the elderly.…”
mentioning
confidence: 99%
“…However, there is evidence to suggest that exercise reduces risk factors associated with CVD, such as obesity and elevated blood pressure, among others (7). Importantly, the protective effects of exercise are not always associated with risk reduction (21,61). This is exemplified in animal models, which are devoid of confounding risk factors for cardiovascular disease, where exercise has consistently been shown to improve coronary vascular reactivity, decrease myocardial stunning, and reduce arrhythmias in hearts subjected to I/R injury (26).…”
Section: Cardioprotective Effects Of Exercisementioning
confidence: 99%
“…The good news is that, for the most part, with the exception of age, gender, and genetics, the other major risk factors for developing CVD can be targeted with preventive measures. For instance, numerous studies have linked a reduction in the rate of initial coronary artery disease events in physically active individuals (61). Coupling this with the experimental and clinical evidence demonstrating the cardioprotective effects of regular activity (9) provides a strong body of evidence that exercise reduces the risk of CVD events (39).…”
mentioning
confidence: 99%
“…Exercise has been identified as one of the most important behavioural strategies for cardiovascular disease prevention, and sedentary individuals (like RA sufferers) will benefit by just a slight increase in physical activity [16,17]. Previous studies in non-RA groups demonstrated that exercise will improve autonomic function (as measured by heart rate variability (HRV)) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%